Factors associated with dental care utilization among Iranian adult populations based on Anderson model - Ashkan Negintaji Zardak; Mostafa Amini-Rarani; Ibrahim Abdollahpour; Faezeh Eslamipour; Bahareh Tahani (BMC Public Health)
Abstract Background The utilization of dental care is affected by different factors. Despite the importance of dental care, there are significant disparities in its utilization among various population groups. The aim of this study was to identify the main factors of dental care utilization and the influences of the Health Transformation Plan (HTP) in Iran based on the Anderson model. Methods and materials This cross-sectional house-by-house study was conducted during Aug-Nov 2022 among 704 adult people in two cities under the coverage of the HTP and two cities out-side the plan using a multi-stage sampling method. Dental visit in the last year was considered as the utilization of the dental services. Independent Factors included the contextual, individual enabling, individual predisposing and individual need factors based on the Andersen model. Personal health behaviors were also assessed. Statistical analysis was conducted using Chi-square tests, simple and multivariable logistic regression models (α < 0.05). Results The 63.1% of the participants covered by the HTP and 57.7% of the population outside the plan sought dental care in the past year. In the final model individuals in the 35–44 age group (OR = 1.5, 95% CI = 1.02–2.2), males (OR = 1.7, 95% CI = 1.2–2.5), single individuals (OR = 1.4, 95% CI = 1.01-2) and those with the perception of need for dental treatment (OR = 2.1, 95% CI = 1.3–3.4) had higher chance of dental visit. Better perceived oral health status was associated with lower chance of visiting the dentist (OR = 0.9, 95% CI = 0.8–0.9). Being covered by the HTP was not significantly in association with the chance of dental visit in the last year (p value = 0.19, OR = 0.78, 95%CI = 0.55–1.12). Conclusion The predisposing factors including age, gender, marital status, and perceived oral health status and perceptions of dental need were the main factors in association with the dental utilization behavior among adults and the coverage by the HTP did not have significant effect on it.